Identifikasi Patotipe Xanthomonas oryzae pv. oryzae dari Tanaman Padi di Sulawesi Selatan - Asysyuura, Asysyuura; Nawangsih, Abdjad Asih; Mutaqin, Kikin Hamzah; Sudir, Sudir (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Xanthomonas oryzae pv. oryzae is the causal agent of bacterial leaf blight (BLB), one of important constraint in rice production. The pathogen is known to have many pathotypes which caused difficulties in disease control. This research was conducted to determine the distribution of X. oryzae pv. oryzae’s pathotypes in seven districts in South Sulawesi. Grouping of pathotypes was performed according to Kozaka method, i.e. based on the response of differential rice varieties. Infection of X. oryzae pv. oryzae was confirmed by PCR using specific primers XOR-R2/XOR-F. Out of 36 isolates, 29 isolates were identified as X. oryzae pv. oryzae which belong to pathotype III (6 isolates), pathotype IV (21 isolates), and pathotype XII (2 isolates). This result indicated that X. oryzae pv. oryzae pathotype IV was distributed widely in South Sulawesi.